Policy Optimization for Hainan Tropical Rainforest National Park Based on Quantitative Comparison of Regional Policies of Free Trade Port Areas - Wang, Hong; Zeng, Yaxue (Frontiers in Environmental Science, 2022)
Hainan Tropical Rainforest National Park, as one of the first national parks established in China, should make full use of the gold brand of “Hainan Free Trade Port” and “National Park,” rely on the advantages and potential of system integration and innovation, draw on the experience of national parks in mature free trade ports (FTPs), and build a perfect national park policy system. This study introduces the PMC index model, constructs a national park policy evaluation index system, and conducts a systematic comparative analysis of 14 representative national park policies in Hainan rainforest, Hong Kong, and Singapore. The study finds that the policy of Hainan Tropical Rainforest National Park is not effective enough, the policy in social and cultural fields is relatively lacking, the policy content needs to be further strengthened, and the policy functions need to be improved, etc., and puts forward corresponding suggestions for optimization.